Flynn's log 1 : Rescue Island - Marshall, Stone ([United States] : Stone Marshall Publishing, 2014)
Flynn's memory is hazy. He wakes up in a strange world and faces two huge surprises. First, his body has transformed. He is no longer a human. He is a Minecraft character! Second, he is totally alone. Will Flynn survive? How did he get in Minecraft? Can he get out?
Keywords: Minecraft (Game) -- Juvenile fiction; Video games -- Juvenile fiction; Fiction